Role and place of innovations in realization of programs of power savings in economy (Путеводитель предпринимателя)
In article modern approaches to increase of power efficiency of economy with use of innovations are analysed. The role of innovations in stimulation of processes of power savings at regional level is shown. The basic directions of perfection of an infrastructure of distribution of innovations in the field of power savings are offered.